2022
DOI: 10.1101/2022.09.19.508437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread, perception-related information in the human brain scales with levels of consciousness

Abstract: How does the human brain generate coherent, subjective perceptions—transforming yellow and oblong visual sensory information into the perception of an edible banana? This is a hard problem. The standard viewpoint posits that anatomical and functional networks somehow integrate local, specialized processing across the brain to construct unique percepts. Here, we provide evidence for a novel organizational concept: we uncover task-specific information distributed across the human brain. We use functional magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…This finding is in agreement with real brain lesion studies showing that lesions in key pain-related areas do not disrupt pain intensity perception (Knecht et al, 1996; Starr et al, 2009). Recent studies also demonstrated that pain can be decoded from nearly all brain areas (Vigotsky et al, 2022). Altogether, our observation supported the notion that pain is represented in a distributed neural system, rather than local and isolated regions (Coghill, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with real brain lesion studies showing that lesions in key pain-related areas do not disrupt pain intensity perception (Knecht et al, 1996; Starr et al, 2009). Recent studies also demonstrated that pain can be decoded from nearly all brain areas (Vigotsky et al, 2022). Altogether, our observation supported the notion that pain is represented in a distributed neural system, rather than local and isolated regions (Coghill, 2020).…”
Section: Discussionmentioning
confidence: 99%